Importance of inflammatory marker ratio and lipid profile ratio in Acute Ischemic Stroke - Mathew John; Leena C.O.; Mahendra Kumar Varma; Harisuthan T.; Evelyn Maria (International Journal of Brain Sciences, 2024)
Background: Acute Ischemic Stroke is a chronic inflammatory disease that is projected to be one of the leading causes of mortality affecting millions of people globally. It is essential to study the Platelet lymphocyte ratio (PLR), Neutrophil lymphocyte ratio (NLR) ratios and C reactive protein (CRP) in impacting the inflammatory status during stroke. It is also important that altered lipid metabolism could influence the inflammatory conditions associated with AIS. Hence analysing the relevance of lipid ratio and inflammatory ratio in the context of AIS is important to understand the pathophysiology of disease. Methodology: The blood was collected from the participants for biochemical and hematological analysis such as lipid profile, CRP and Complete blood count for the quantitation of NLR and PLR. Results: The groups involved in the study are AIS and healthy controls. The sample size for this study was n=151 in both AIS and control group .Inflammatory markers such as NLR, PLR, CRP and lipid profile ratio, TG/HDL-C and systolic & diastolic BPs where the parameters considered for comparison between control and AIS groups. The results revealed that there was significant differences in NLR, CRP, TG/HDL-C and BP between the study groups (p value<0.01). PLR value did not significantly altered between the groups (P=0.5). Conclusion: The result showed that inflammatory markers, lipid profile and blood pressure play vital role in the occurrence of acute ischemic stroke.
Keywords: haematological; inflammation; neutrophils; platelets; triglycerides